2021
DOI: 10.3389/fonc.2020.604534
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DNAJC3-AS1 Regulates Fatty Acid Synthase via the EGFR Pathway to Promote the Progression of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide. Recent studies have shown that long non-coding RNAs (lncRNAs) are involved in tumorigenesis and the development of CRC. By constructing a differential lncRNA expression profile, we screened gene chips and found that DNAJC3-AS1 was highly expressed in CRC tissues and was associated with poor prognosis in patients with CRC. Further, we proved through assays such as wound healing, colony formation, and Cell Counting Kit-8 (CCK8) that interfering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
0
21
0
2
Order By: Relevance
“…DNAJC3-AS1 is an oncogenic lncRNA characterized in several types of cancers. [15][16][17] In colorectal cancer, its expression is increased. DNAJC3-AS1 overexpression interacts with epidermal growth factor receptor (EGFR) pathway to regulate fatty acid synthase, thereby promoting cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNAJC3-AS1 is an oncogenic lncRNA characterized in several types of cancers. [15][16][17] In colorectal cancer, its expression is increased. DNAJC3-AS1 overexpression interacts with epidermal growth factor receptor (EGFR) pathway to regulate fatty acid synthase, thereby promoting cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…DNAJC3-AS1 overexpression interacts with epidermal growth factor receptor (EGFR) pathway to regulate fatty acid synthase, thereby promoting cancer progression. 15 DNAJC3-AS1 expression is also increased in renal cell carcinoma, and it sponges miR-27a-3p to upregulate PRDM14, thereby accelerating cancer development. 16 DNAJC3-AS1 interacts with its sense-cognate gene 17 In the present study, we observed the upregulation of DNAJC3-AS1 in HCC and its role in enhancing cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The malonyl-CoA produced under the action of ACC1 mainly promotes the synthesis of FAs, while the malonyl-CoA produced under the action of ACC2 mainly inhibits the oxidation of FAs [84], keeping the FA content in the body at a high level. To further meet the needs of tumor cells, ACC is highly expressed in NSCLC [85], cervical squamous cell carcinoma [86] and colorectal cancer [87].…”
Section: Acetyl-coa Carboxylasementioning
confidence: 99%
“…The mechanisms by which lncRNAs regulate ACC in different tumors are also different. LncRNA DNAJC3-AS1 is highly expressed in colorectal cancer and can regulate the expression of ACC and FASN by activating PI3K/AKT, a recognized oncogenic pathway, thereby promoting tumor progression [87]. Recent studies have demonstrated that lncRNA CTD-2245E15.3 is highly expressed in NSCLC, and its inhibition can regulate lipid metabolism-related genes.…”
Section: Acetyl-coa Carboxylasementioning
confidence: 99%